THE EVALUATION OF CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) MODEL FOR ENGLISH LANGUAGE LEARNING IN MTSN 5 NGANJUK - RONA MERITA (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2024)
The aim of this study was to find out the application of the implementation of Englishlanguage learning based on the Merdeka Curriculum at MTsN 5 Nganjuk with the evaluation of theCIPP (Context, Input, Process, Product) model. This research is qualitative research that uses theCIPP model by evaluating each component of the context, input, process and product to achieve aneffective learning process. Sources of research data were English language teachers, curriculumrepresentatives, and school principals at MTsN 5 Nganjuk. Data collection using observationinstruments, documentation, and interviews. The data is analyzed by descriptive qualitative.The study reveals that the context, input, process, and product components in Englishlanguage learning at MTsN 5 Nganjuk are overall good. Context evaluation, covering school profile,teacher preparation, learning activities, observations, and teacher feedback, is rated positively. Inputevaluation shows the teaching staff’s educational background (Bachelor's and master’s in education)and material mastery as good, though teachers sometimes overly rely on textbooks. Informationtechnology is used but infrequently, and facilities adequately meet both student and teacher needs.The process evaluation indicates that planning and implementing English language learning in theMerdeka Curriculum is fairly effective. Product evaluation through formative and summativeassessments highlights listening as the most mastered skill, with writing as the least.Keywords: Evaluation model, CIPP, Merdeka curriculum.